Les outils multimédia d'aide à l'apprentissage des langues : de l'évaluation à la réflexion prospective - Maguy Pothier; Anne Iotz; Christine Rodrigues (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
In this article, we present the results of the evaluation of a multimedia software CAMILLE Travailler en France that we had designed. We then started a prospective reflection on what could be supportive multimedia language learning environments really meeting learners´ needs. As the experimentation revealed certain lacks in the environment, we tried to find out their causes before going further in the design process. We started from the following statement: since Information and Communication Technologies (ICT) cannot succeed everywhere in which area can they be useful or even irreplaceable? We will first present CAMILLE and we will briefly describe the evaluation methodology we have adopted. We will then specify which precise questions the experimentation sought to answer. We will try to understand if the software made the students progress in their general knowledge of the language - more specifically in oral and writing comprehension - by taking into account their effective learning test results. Finally, we will define few elements which should be considered while designing new multimedia aid tools for language learning.